2014
DOI: 10.1111/ijfs.12482
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pepsin hydrolysis on the soy β‐conglycinin aggregates formed by heat treatment at different pH

Abstract: Summary The effects of pepsin hydrolysis on the β‐conglycinin aggregates formed by heat treatment at different pH were investigated. Results showed that fibrils were still observed, whereas the random aggregates were easily to be digested in the simulated gastric fluid. Electrophoresis and molecular weight analysis indicated that large aggregates still existed after pepsin treatment for fibrils. Hydrolysis resulted in changes in the apparent viscosity (ηapp) of 6% fibril solutions. The ηapp at the shear rate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Compared with the core region, the extension regions were hydrophilic, rich in aspartic acid, and were disrupted easily by proteases. 25,26 Moreover, with the decrease in band intensity of the ⊍ and ⊍ 0 subunits, the band intensity of 47 kDa and H 1 increased (Fig. 5 (B)).…”
Section: Binding Of ⊎-Conglycinin With Epitope Polyclonal Antibodiesmentioning
confidence: 88%
“…Compared with the core region, the extension regions were hydrophilic, rich in aspartic acid, and were disrupted easily by proteases. 25,26 Moreover, with the decrease in band intensity of the ⊍ and ⊍ 0 subunits, the band intensity of 47 kDa and H 1 increased (Fig. 5 (B)).…”
Section: Binding Of ⊎-Conglycinin With Epitope Polyclonal Antibodiesmentioning
confidence: 88%
“…This assay was performed to isolate the protein from the butternut squash seed sample according to a previously described procedure (He, Yang, & Zhang, 2014), with some modifications. The properties of these purified protein can be evaluated through following assays.…”
Section: Extraction Of Proteinmentioning
confidence: 99%
“…Previous assay performed by He et al (2014) found that a fresh pepsin solution (20 mg/ml in SGF solution) stirred with a magnetic stirrer for 10 min before it was centrifuged using a MiniSpin centrifuge (Eppendorf) at 10,000 g for 3 min to remove the insoluble substances and then added to these solutions. The final concentration of pepsin was 2 mg/ml.…”
Section: Pepsin Hydrolysismentioning
confidence: 99%
“…1.0-2.5) [1][2][3][4] is a proteolytic enzyme secreted by the chief cells of gastric mucosa, which is responsible for the digestion of proteins in the stomach [5]. Pepsin is extensively used in the food Article Related Abbreviations: 4VP, 4-vinylpyridine; DA, dopamine hydrochloride; IS, ionic strength; MOXA, 2-methyl-2-oxazoline; P4VP, poly(4-vinylpyridine); PAA, poly(acrylic acid); PDA, polydopamine; PMOXA, poly(2-methyl-2-oxazoline); SEF, sensitivity enhancement factor; XPS, X-ray photoelectron spectrometer industry [6][7][8], such as in cheese making as the coagulating enzyme, in beer production as the immobilized enzyme for haze prevention, and in soy production as the hydrolytic enzyme to hydrolyze soy protein. In addition, pepsin has also been studied from medical aspects as a reliable indicator for the diagnosis of laryngopharyngeal reflux disease [9][10][11], because pepsin is produced only in the stomach and all refluxate contains it [12].…”
Section: Introductionmentioning
confidence: 99%
“…1.0–2.5) [1–4] is a proteolytic enzyme secreted by the chief cells of gastric mucosa, which is responsible for the digestion of proteins in the stomach [5]. Pepsin is extensively used in the food industry [6–8], such as in cheese making as the coagulating enzyme, in beer production as the immobilized enzyme for haze prevention, and in soy production as the hydrolytic enzyme to hydrolyze soy protein. In addition, pepsin has also been studied from medical aspects as a reliable indicator for the diagnosis of laryngopharyngeal reflux disease [9–11], because pepsin is produced only in the stomach and all refluxate contains it [12].…”
Section: Introductionmentioning
confidence: 99%